Clinical advances of siRNA therapeutics - Hu, Bo; Weng, Yuhua; Xia, Xin‐Hua; Liang, Xing‐jie; Huang, Yuanyu (The journal of gene medicine, 2019)
Small interfering RNA (siRNA) enables efficient target gene silencing by employing a RNA interference (RNAi) mechanism, which can compromise gene expression and regulate gene activity by cleaving mRNA or repressing its translation. Twenty years after the discovery of RNAi in 1998, ONPATTRO™ (patisiran) (Alnylam Pharmaceuticals, Inc.), a lipid formulated siRNA modality, was approved for the first time by United States Food and Drug Administration and the European Commission in 2018. With this milestone achievement, siRNA therapeutics will soar in the coming years. Here, we review the discovery and the mechanisms of RNAi, briefly describe the delivery technologies of siRNA, and summarize recent clinical advances of siRNA therapeutics.